Penggunaan Jargon dalam Bela Diri Aikidou Jepang di Media Sosial Instagram - I Made Wahyu Dwi Prananta I Made Wahyu Dwi Prananta; Made Henra Dwikarmawan Sudipa Sudipa (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2024)
Abstract This study aims to understand the significance of the forms and meanings of Aikido martial arts jargon on Instagram. Jargon refers to specialized vocabulary used within a particular field, and due to its very specific forms and meanings, it is often not understood by those outside the field. Data was collected from words and texts on Instagram through two accounts: Aiki.Master with 105 thousand followers and Bulungan_aikido with 28.2 thousand followers. A qualitative descriptive method was employed to analyze the collected data and identify specific terms or phrases frequently used by Japanese Aikido practitioners. Data analysis utilized Halligan's (2004) theory of jargon formation and Leech's (1981) theory of meaning. The analysis identified five Aikido jargon terms on Instagram, each with distinct forms and meanings, including both denotative and connotative aspects. The findings illustrate how Aikido jargon is not only formed through training practices but also reflects variations in meaning depending on the context of its use within the Aikido community.